IDENTIFIKASI FAKTOR SEBARAN MACAN DAHAN (Neofelis diardi Cuvier, 1823) DI EKOSISTEM RAWA GAMBUT, TAMAN NASIONAL SEBANGAU - Kuncahyo, Bantista Adies; Alikodra, Hadi S.; Gunawan, Hendra (Media Konservasi, 2016)
The Sunda clouded leopard (Neofelis diardi Cuvier, 1823) is the largest predator and the keystone species on Borneo Island. Therefore, the existence of N. diardi is very important to maintain the stability and healthy of ecosystems in Kalimantan Forest. Sebangau National Park (SNP), Central Kalimantan Province is one of the important habitats for this species because it is formed by peat swamp ecosystem and it has function to maintain the balance of the global climate. Data of the distribution factors of N. diardi were expected to used for monitoring and inventorying of population this species, especially in SNP. Data collection was conducted from June until November 2014 through methods of 12 track-sets; 9 units camera traps; and signs of animal presence likely footprints, feces, claws, scratches, scrapes, and vocalizations in 2 grids, each size 6 x 6 km2. This study results show that the distribution of N. diardi is affected by five factors namely, the distance from water source (P = 0,002); the distance from the potential of disturbance (P = 0,017); forest canopy density (P= 0,04); peat depth (P = 0,002); and habitat types in the SNP (P = 0,011). Only the altitude factor does not affect the distribution of N. diardi (P = 0,064) at SNP. Furthermore, this study also indicates that the presence and abundance of animal preys as another factor affecting the distribution of N. diardi at SNP. This condition is caused by the tendency of N. diardi encounter in a RAI values of animal preys on medium-grade (9,38; 10,53) and high (14,52; 18,60; 18,60). Finally, this study also demonstrates that the existence of N. diardi can be considered as an indicator species for forest in good condition. Keyword : keystone species, Neofelis diardi, peat swamp ecosystem, top predator